2017
DOI: 10.3390/jof3010002
|View full text |Cite
|
Sign up to set email alerts
|

Biocontrol Properties of Basidiomycetes: An Overview

Abstract: In agriculture, there is an urgent need for alternate ecofriendly products to control plant diseases. These alternate products must possess preferable characteristics such as new modes of action, cost effectiveness, biodegradability, and target specificity. In the current scenario, studies on macrofungi have been an area of importance for scientists. Macrofungi grow prolifically and are found in many parts of the world. Basidiomycetes (mushrooms) flourish ubiquitously under warm and humid climates. Basidiomyce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 86 publications
0
18
0
1
Order By: Relevance
“…Aside from low molecular metabolites, they contain beta-glucans and other oligomers that constitute the active ingredients of medicinal mushrooms [ 3 , 4 , 85 , 86 , 87 ]. The Physalacriaceae are known to produce manifold antibiotics from mycelial cultures [ 8 , 88 ], but can also produce polysaccharides with anticancer, antihypertensive, anti-inflammatory and hemagglutination activities [ 89 , 90 , 91 , 92 ]. Many studies have documented the bioactivities of these mushrooms; however, most were inconclusive since they did not go further in identifying the active principles using chromatography and spectral techniques, such as mass spectrometry and nuclear magnetic resonance (NMR) spectroscopy.…”
Section: Bioactivities and Mode Of Actionmentioning
confidence: 99%
“…Aside from low molecular metabolites, they contain beta-glucans and other oligomers that constitute the active ingredients of medicinal mushrooms [ 3 , 4 , 85 , 86 , 87 ]. The Physalacriaceae are known to produce manifold antibiotics from mycelial cultures [ 8 , 88 ], but can also produce polysaccharides with anticancer, antihypertensive, anti-inflammatory and hemagglutination activities [ 89 , 90 , 91 , 92 ]. Many studies have documented the bioactivities of these mushrooms; however, most were inconclusive since they did not go further in identifying the active principles using chromatography and spectral techniques, such as mass spectrometry and nuclear magnetic resonance (NMR) spectroscopy.…”
Section: Bioactivities and Mode Of Actionmentioning
confidence: 99%
“…One of the most unknown characteristics of Pleurotus mushrooms is their ability to kill and feed on living nematodes ( Thorn and Barron 1984 ) and therefore their potential for the biocontrol of parasitic nematodes ( Degenkolb and Vilcinskas 2016 ; Sivanandhan et al 2017 ; Castañeda-Ramírez et al 2020 ). Although a few compounds produced by Pleurotus have been reported to cause paralysis in nematode worms ( Kwok et al 1992 ; Satou et al 2008 ), a more recent study has suggested that the true identity of the toxins targeting nematodes remains to be discovered ( Lee et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…One of the most unknown characteristics of Pleurotus mushrooms is their ability to kill and feed on living nematodes (Thorn and Barron 1984) and therefore their potential for the biocontrol of parasitic nematodes (Degenkolb and Vilcinskas 2016; Sivanandhan et al 2017;Castañeda-Ramírez et al 2020). Although a few compounds produced by Pleurotus have been reported to cause paralysis in nematode worms (Kwok et al 1992;Satou et al 2008), a more recent study has suggested that the true identity of the toxins targeting nematodes remain to be discovered (Lee et al 2020).…”
Section: Introductionmentioning
confidence: 99%